2015
DOI: 10.1051/0004-6361/201525797
|View full text |Cite
|
Sign up to set email alerts
|

Stellar parameters of early-M dwarfs from ratios of spectral features at optical wavelengths

Abstract: Context. Low-mass stars have been recognised as promising targets in the search for rocky, small planets with the potential of supporting life. As a consequence, Doppler search programmes using high-resolution spectrographs like HARPS or HARPS-N are providing huge quantities of optical spectra of M dwarfs. However, determining the stellar parameters of M dwarfs using optical spectra has proven to be challenging. Aims. We aim to calibrate empirical relationships to determine accurate stellar parameters for earl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
99
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 80 publications
(108 citation statements)
references
References 57 publications
(108 reference statements)
9
99
0
Order By: Relevance
“…They showed that the calibration of Casagrande et al (2008) underestimates temperatures because Casagrande et al (2008) assumed M dwarfs to be blackbodies, but M dwarfs have more flux in the infrared than predicted for a blackbody. For metallicities, however, Maldonado et al (2015) reported good agreement of their results with Neves et al (2012) and Neves et al (2014).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…They showed that the calibration of Casagrande et al (2008) underestimates temperatures because Casagrande et al (2008) assumed M dwarfs to be blackbodies, but M dwarfs have more flux in the infrared than predicted for a blackbody. For metallicities, however, Maldonado et al (2015) reported good agreement of their results with Neves et al (2012) and Neves et al (2014).…”
Section: Introductionmentioning
confidence: 90%
“…Their results in metallicity agree excellently well with those of Rojas-Ayala et al (2012), with mean differences of 0.03 dex. A recent work by Maldonado et al (2015) used pseudo-equivalent widths of optical spectra to determine effective temperature and [Fe/H]. They showed that the calibration of Casagrande et al (2008) underestimates temperatures because Casagrande et al (2008) assumed M dwarfs to be blackbodies, but M dwarfs have more flux in the infrared than predicted for a blackbody.…”
Section: Introductionmentioning
confidence: 99%
“…We used the stellar parameters published by Maldonado et al (2017), which were calculated applying the empirical relations by Maldonado et al (2015) on the same HARPS-N spectra from which we derived the RV time series. This technique calculates stellar temperatures from ratios of pseudo-equivalent widths of spectral features, and calibrate the metallicity on combinations and ratios of different features.…”
Section: Stellar Properties Of Gl15a and Gl15bmentioning
confidence: 99%
“…This technique calculates stellar temperatures from ratios of pseudo-equivalent widths of spectral features, and calibrate the metallicity on combinations and ratios of different features. Although such techniques are mainly used for solar-type stars, Maldonado et al (2015) proved them to be equally effective for low-mass stars. Howard et al (2014) derived a rotational period of 43.82 ± 0.56 d, both from their Keck-HIRES measurements of the S HK index and their APT photometric observations at Fairborn Observatory.…”
Section: Stellar Properties Of Gl15a and Gl15bmentioning
confidence: 99%
“…The data analyzed in this paper have been collected during 7 semesters, from September 2012 to February 2016. In Maldonado et al (2016) we have measured the stellar parameters using the methodology described in Maldonado et al (2015). The most relevant stellar parameters for the current analysis are listed in Table 1.…”
Section: Target Selectionmentioning
confidence: 99%